Oxygen evolution catalyst based on metal organic framework as well as synthesis method and application of oxygen evolution catalyst

Through dynamic reconstruction mechanism and dynamic process, a new oxygen evolution catalyst including metal organic frames and pore structure modification units was designed, which solved the problem of high overpotential of oxygen evolution reactions in electrochemical water decomposition and achieved efficient and stable catalytic performance.

CN119710818AActive Publication Date: 2025-03-28KUNMING UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411917685.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

The prior art has problems of high overpotential and low energy conversion efficiency in the oxygen evolution reaction (OER) in electrochemical water decomposition, and the high cost and scarcity of precious metal catalysts limit their large-scale application.

Method used

Through dynamic reconstruction mechanism and dynamic process, a new oxygen evolution catalyst including metal organic frames and pore structure modification units is designed using metal organic frames (MOFs) materials to reveal the structure-activity relationship of the catalyst surface through in-situ characterization.

Benefits of technology

A highly efficient catalyst that is rich in oxygen-rich vacancies, bond length extension and active site adaptation through self-reconstruction in an alkaline environment is achieved, which improves the performance and stability of the catalyst, exceeds most reported anode catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710818A_ABST
    Figure CN119710818A_ABST
Patent Text Reader

Abstract

The invention discloses an oxygen evolution catalyst based on a metal organic framework as well as a synthesis method and application of the oxygen evolution catalyst. The oxygen evolution catalyst comprises a metal organic framework and a pore structure modification unit inserted into the metal organic framework, the metal organic framework is formed by combining, coordinating and connecting an organic ligand A containing dicarboxylic acid and a metal source reagent M1, and the pore structure modification unit is formed by combining, coordinating and connecting a triazole organic ligand B and a metal source reagent M2; wherein the dicarboxylic acid-containing organic ligand A is one or more of compounds shown in formula (I), and the triazole organic ligand B is one or more of compounds shown in formula (II): # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an oxygen evolution catalyst based on metal organic frameworks (MOFs), a synthesis method thereof and application of the catalyst in oxygen evolution reaction by electrolysis of water. Background Art

[0002] Electrochemical water splitting is an effective way to produce high-purity hydrogen. However, in the anode half-reaction, the oxygen evolution reaction (OER) requires a larger overpotential than the cathode hydrogen evolution reaction (HER) due to multi-step proton / electron coupling, which hinders the efficient conversion of energy. Among them, precious metal catalysts such as Ru and Ir oxides can significantly reduce the overpotential of OER, but their high price and scarce reserves severely limit their large-scale industrial application. In contrast, MOFs materials are regarded as a promising OER catalyst due to their structural flexibility and tunability. However, MOFs materials are usually prone to structural transformation in the OER reaction, which makes it very challenging to accurately study their structure-property relationship.

[0003] Dynamic reconstruction refers to the process of structural changes occurring on the surface of a catalyst or material. In catalytic reactions, dynamic reconstruction can cause changes in the activity and selectivity of the catalyst, thereby affecting the efficiency of the reaction and the distribution of products. Dynamic reconstruction usually occurs at high temperature, high pressure or specific reaction conditions, involving processes such as adsorption, dissociation, diffusion and recombination. These processes cause the surface atoms to rearrange and form new crystal structures or surface phases. The mechanism and process of dynamic reconstruction depend on factors such as the composition, morphology and reaction conditions of the catalyst. Dynamic reconstruction has an important influence on catalytic reactions. First, it can change the distribution of active sites and surface energy of the catalyst, thereby regulating the rate and selectivity of the reaction. Second, dynamic reconstruction can change the interaction between the catalyst and the reactants, affecting the rate and energy barrier of reaction steps such as adsorption, dissociation and diffusion. In addition, dynamic reconstruction can also regulate the stability and life of the catalyst. Therefore, understanding and controlling dynamic reconstruction is crucial for designing efficient catalysts and optimizing catalytic reactions.

[0004] In order to overcome the current development bottleneck of electrochemical performance, it is still urgent to effectively utilize the reconstruction behavior of MOFs, optimize the catalyst structure design and realize the precise synthesis of efficient catalysts. The present invention aims to analyze the structural evolution and in-situ self-reconstruction mechanism of MOFs to improve their intrinsic activity, and establish the mechanism of MOFs structural change and the relationship between structure and performance during the OER process. This will provide specific guidance for structural regulation, thereby improving the performance and stability of catalysts. Summary of the invention

[0005] The present invention intends to reveal the structure-activity relationship of the catalyst surface through in-situ characterization based on dynamic reconstruction mechanism and kinetic process, and obtain a highly efficient electrocatalytic oxygen evolution catalyst. At the same time, by regulating the composition and structural coordination environment of the catalyst, the surface reconstruction can be controlled to optimize the efficiency and selectivity of the catalytic reaction.

[0006] The first aspect of the present invention discloses an oxygen evolution catalyst based on a metal organic framework, wherein the oxygen evolution catalyst comprises a metal organic framework and a pore structure modification unit inserted into the metal organic framework, wherein the metal organic framework is formed by a combination of an organic ligand A containing a dicarboxylic acid and a metal source reagent M1, and the pore structure modification unit is formed by a combination of a triazole organic ligand B and a metal source reagent M2, wherein the organic ligand A containing a dicarboxylic acid is one or more of the compounds represented by formula (I), and the triazole organic ligand B is one or more of the compounds represented by formula (II):

[0007]

[0008] in:

[0009] In formula (I), the combination of R1 / R2 / R3 / R4 is A1: H / H / H / H; A2: OH / H / H / H, A3: SH / H / H / H, A4: NH2 / H / H / H, A5: NO2 / H / H / H, A6: Br / H / Br / H, A7: OH / H / OH / H, A8: Cl / H / Cl / H, A9: F / F / F / F, A10: NHCHO / H / H / H, A11: Cl / H / H / H, A12: Br / H / H / H, A13: NH2 / H / NH2 / H, A14: Br / H / H / H or A15: Cl / H / H / H;

[0010] The combination of R5 / R6 in formula (II) is B1: H / H, B2: H / NH2, B3: H / NO2, B4: H / SH, B5: SH / CH3, B6: SH / NH2, B7: H / CH3, B8: H / CF3, B9: H / Br, B10: H / CN, B11: CH3 / CH3 or B12: NH2 / NH2.

[0011] In the present invention, M1 is a metal or a combination of different metal ions that can form a trimer, M2 is a metal or a combination of different metal ions that can form a triazole dimer, [(M1)3O(A)3] formed by the coordination connection of the dicarboxylic acid-containing organic ligand A and the metal source reagent M1 is a MIL-88B network MOF structure, triazole is a pore separator ligand, and the pore structure modification unit [(M2)2(B)3X6] (X=H2O or Cl -) is a triazole dimer network MOF structure, [(M2)2(B)3X6] is inserted into the MIL-88B network MOF structure. The metal source reagent M1 and the metal source reagent M2 can be the same or different.

[0012] Furthermore, the metal source reagent M1 is an Fe salt, and the metal source reagent M2 is one or more of a Fe salt, a Fe salt, a Ni salt, a Co salt and a Mn salt.

[0013] Furthermore, the metal source reagent M1 is FeCl3, and the metal source reagent M2 is one or more of FeCl2, FeCl3, Fe(NO3)2, Ni(NO3)2, Mn(OAc)2 and Co(OAc)2.

[0014] Furthermore, the dicarboxylic acid-containing organic ligand A is 2-hydroxyterephthalic acid, and the triazole organic ligand B is 1,2,4-triazole or 3-amino-5-mercapto-1,2,4-triazole.

[0015] The second aspect of the present invention discloses a method for synthesizing the aforementioned oxygen evolution catalyst, comprising the following steps:

[0016] Step (1): adding an organic ligand A containing a dicarboxylic acid, a triazole organic ligand B, a metal source reagent M1 and a metal source reagent M2 into an organic solvent S, and dissolving them to obtain a mixed solution a;

[0017] Step (2): adding a synthesis reagent Q to the mixed solution a to obtain a mixed solution b;

[0018] Step (3): subjecting the mixed solution b to a hydrothermal reaction at a temperature of 140 to 160° C. for 24 to 72 hours, and subjecting the product to solid-liquid separation, washing and drying.

[0019] Furthermore, in step (1), the molar ratio of the dicarboxylic acid-containing organic ligand A to the triazole organic ligand B is 1:1 to 1.2, preferably 1:1.

[0020] Furthermore, the organic solvent S is N,N-dimethylformamide, and its usage is 10 to 15 times of the total mass of the organic ligand A containing dicarboxylic acid and the organic ligand B containing triazole, preferably 15 times.

[0021] Furthermore, in step (2), the synthesis reagent Q is trifluoroacetic acid, and the mass ratio of the synthesis reagent Q to the organic ligand A of the dicarboxylic acid and the triazole organic ligand B is A+B:Q=1:1.2-1.9.

[0022] Furthermore, the synthesis method further comprises the following step (4): using the metal organic framework powder material obtained in step (3) to make a working electrode, and using a three-electrode system to perform cyclic voltammetry cycles under alkaline environmental conditions to dynamically reconstruct the metal organic framework material. The three-electrode system uses a platinum sheet as a comparative electrode and mercury / mercuric oxide as a reference electrode; and performs cyclic voltammetry (CV) cycles under 1.0 mol / L potassium hydroxide solution environmental conditions at an applied voltage of 1.1 to 1.6 V vs. RHE.

[0023] Furthermore, in step (3), a conductive substrate can be added into a hydrothermal reaction vessel (e.g., a Teflon stainless steel reaction vessel) so that the synthesized metal organic framework powder material is loaded / attached to the conductive substrate to directly form an electrode. The conductive substrate can be nickel foam, carbon brazing paper or copper sheet, preferably nickel foam.

[0024] The third aspect of the present invention discloses the use of the above oxygen evolution catalyst in the oxygen evolution reaction by electrolysis of water.

[0025] Compared with the prior art, the technical solution of the present invention has the following advantages:

[0026] The oxygen evolution catalyst of the present invention has a novel framework structure of [(M1)3O(A)3][(M2)2(B)3X6], comprising a [(M1)3O(A)3] metal organic framework and a pore structure modification unit [(M2)2(B)3X6] inserted into the metal organic framework, wherein the introduction of the pore structure modification unit [(M2)2(B)3X6] can stabilize the structure of the [(M1)3O(A)3] metal organic framework, and [(M1)3O(A)3][(M2)2(B)3X6] with the novel framework structure can form oxygen-rich vacancies, bond length extension and active site adaptation under alkaline and applied voltage conditions to efficiently catalyze oxygen evolution, so that the catalyst undergoes reasonable dynamic reconstruction, which affects its kinetic behavior and ensures long-term high-activity industrial stability, exceeding the catalytic activity and industrial stability of most reported anode catalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Middle: a, b and c are the XRD spectra of [Fe3O(A2)3], [Fe3O(A2)3][Fe2(B1)3X6] and [Fe3O(A2)3][Ni2(B1)3X6], d, e and f are the XRD spectra of [Fe3O(A2)3], [Fe3O(A2)3][Fe2(B1)3X6] and [Fe3O(A2)3][Ni2(B1)3X6] after being placed in water environment for 1 day;

[0028] Figure 2a is the FT-IR spectrum of [Fe3O(A2)3][Ni2(B1)3X6] and its FT-IR spectrum after being placed in a water environment for 1 day, b is the FT-IR spectrum of [Fe3O(A2)3] and its FT-IR spectrum after being placed in a water environment for 1 day;

[0029] Figure 3 N2 adsorption-desorption isotherms of [Fe3O(A2)3][Ni2(B1)3X6] and [Fe3O(A2)3];

[0030] Figure 4 a, b and c are SEM images of [Fe3O(A2)3], [Fe3O(A2)3][Fe2(B1)3X6] and [Fe3O(A2)3][Ni2(B1)3X6] respectively;

[0031] Figure 5 a and b are the TEM and HRTEM spectra of [Fe3O(A2)3][Ni2(B1)3X6] respectively;

[0032] Figure 6 Fe 2p XPS fine spectra of [Fe3O(A2)3][Ni2(B1)3X6] and [Fe3O(A2)3];

[0033] Figure 7 The Ni 2p XPS fine spectrum of [Fe3O(A2)3][Ni2(B1)3X6] is shown;

[0034] Figure 8 Middle: a is the C1s XPS fine spectra of [Fe3O(A2)3][Ni2(B1)3X6] and [Fe3O(A2)3], and b is the O 1s XPS fine spectra of the two;

[0035] Fig. 9 The VB-XPS fine spectra of [Fe3O(A2)3], [Fe3O(A2)3][Fe2(B1)3X6] and [Fe3O(A2)3][Ni2(B1)3X6] are shown;

[0036] Fig.10 The electrocatalytic oxygen evolution performance diagram of [Fe3O(A2)3], [Fe3O(A2)3][Fe2(B1)3X6] and [Fe3O(A2)3][Ni2(B1)3X6] at the initial stage;

[0037] Fig.11Middle: a is the Raman spectra of [Fe3O(A2)3], [Fe3O(A2)3][Fe2(B1)3X6] and [Fe3O(A2)3][Ni2(B1)3X6] and their Raman spectra after treatment with 1M KOH, b is the in situ Raman spectrum of electrocatalytic oxygen evolution of [Fe3O(A2)3][Fe2(B1)3X6];

[0038] Fig.12 a and b are the in-situ Raman spectra of electrocatalytic oxygen evolution of [Fe3O(A2)3] and [Fe3O(A2)3][Ni2(B1)3X6], respectively;

[0039] Fig.13 a, b and c, d are the CV cycle performance change diagrams of [Fe3O(A2)3] and [Fe3O(A2)3][Ni2(B1)3X6] respectively;

[0040] Fig.14 The electrocatalytic oxygen evolution performance diagram of the synthetic materials in Comparative Examples 2 to 5 of the present invention;

[0041] Fig.15 The catalytic stability diagram of [Fe3O(A2)3] and [Fe3O(A2)3][Ni2(B1)3X6];

[0042] Fig.16 This is the SEM image of [Fe3O(A2)3][Ni2(B1)3X6] after catalytic stability test;

[0043] Fig.17 This is the SEM image of [Fe3O(A2)3] after catalytic stability test;

[0044] Fig.18 AEMWE catalytic performance diagram of IrO2 and [Fe3O(A2)3][Ni2(B1)3X6];

[0045] Fig.19 AEMWE catalytic stability diagram of [Fe3O(A2)3] and [Fe3O(A2)3][Ni2(B1)3X6]. DETAILED DESCRIPTION

[0046] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0047] The materials, reagents, etc. used in the following examples, such as the dicarboxylic acid-containing organic ligand A, triazole organic ligand B, metal source reagent M1, metal source reagent M2, solvents, synthesis reagents, etc. used in the synthesis process are all commercially available products and can be obtained from commercial channels unless otherwise specified.

[0048] Unless otherwise specified, the experimental methods used in the following implementation methods are all conventional experimental methods.

[0049] Unless otherwise specified, the terms used in the following implementation methods and examples generally have the meanings commonly understood by those of ordinary skill in the art.

[0050] According to the rational design method, the present invention uses dicarboxylic acids containing various functional groups as ligands and metal combinations to synthesize the MIL-88B framework [M13O(A)3]. In order to achieve high OER activity, the MIL-88B framework is used as the parent structure, and a pore space partitioning strategy is adopted. The strategy involves inserting a C3-symmetric triazole cluster into the MIL-88B structure and introducing a high-density metal site center, thereby constructing a new framework named [M13O(A2)3][M22(B1)3X6]. In the MIL-88B framework, M1 is a metal or a combination of different metal ions that can form a trimer. In the triazole dimer, M2 is a metal or a combination of metals that can form a triazole dimer, and triazole is a pore separator ligand.

[0051] In the embodiment of the present invention, A is one or more of the dicarboxylic acid-containing organic ligands shown in the following formula (I), and B is one or more of the triazole organic ligands shown in the following formula (II):

[0052]

[0053] in:

[0054] In formula (I), the combination of R1 / R2 / R3 / R4 is A1: H / H / H / H; A2: OH / H / H / H, A3: SH / H / H / H, A4: NH2 / H / H / H, A5: NO2 / H / H / H, A6: Br / H / Br / H, A7: OH / H / OH / H, A8: Cl / H / Cl / H, A9: F / F / F / F, A10: NHCHO / H / H / H, A11: Cl / H / H / H, A12: Br / H / H / H, A13: NH2 / H / NH2 / H, A14: Br / H / H / H or A15: Cl / H / H / H;

[0055] The combination of R5 / R6 in formula (II) is B1: H / H, B2: H / NH2, B3: H / NO2, B4: H / SH, B5: SH / CH3, B6: SH / NH2, B7: H / CH3, B8: H / CF3, B9: H / Br, B10: H / CN, B11: CH3 / CH3 or B12: NH2 / NH2.

[0056] In the embodiment of the present invention, the metal source reagent M1 and the metal source reagent M2 can be the same or different, and their actual usage can be determined based on the theoretical usage, preferably equal to or slightly larger than the theoretical usage.

[0057] Example 1

[0058] Synthesis of Metal-Organic Framework Materials Modified with Pore Structural Units [Fe3O(A2)3][Fe2(B1)3X6]

[0059] In a Teflon stainless steel reaction vessel, FeCl3·6H2O (411.3 mg, ~1.5 mmol), 2-hydroxyterephthalic acid (169.8 mg, ~0.9 mmol, A2 in formula (Ⅰ)) and 1,2,4-triazole (62.2 mg, ~0.9 mmol) were first ultrasonically dissolved in 3.0 g of N,N-dimethylformamide (DMF), and then 320 mg of trifluoroacetic acid (TFA) was added. After magnetic stirring for 2 h, nickel foam (NF) was placed as a conductive substrate, and the Teflon stainless steel reaction vessel was sealed in a stainless steel autoclave and heated in an oven at 150°C for 24 h. After cooling to room temperature, the solid and liquid were separated, and the synthesized [Fe3O(A2)3][Fe2(B1)3X6] was repeatedly washed with DMF and dried at 55°C for 12 h.

[0060] Example 2

[0061] Synthesis of Metal-Organic Framework Materials Modified with Pore Structural Units [Fe3O(A2)3][Ni2(B1)3X6]

[0062] In a Teflon stainless steel reaction vessel, FeCl3·6H2O (251.5 mg, ~0.9 mmol), Ni(NO3)2·6H2O (204.8 mg, ~0.7 mmol), 2-hydroxyterephthalic acid (169.8 mg, ~0.9 mmol) and 1,2,4-triazole (62.2 mg, ~0.9 mmol) were first ultrasonically dissolved in 3.0 g of N,N-dimethylformamide (DMF), and then 320 mg of trifluoroacetic acid (TFA) was added. After magnetic stirring for 2 h, nickel foam (NF) was placed as a conductive substrate, and the Teflon stainless steel reaction vessel was sealed in a stainless steel autoclave and heated in an oven at 150°C for 24 h. After cooling to room temperature, the solid and liquid were separated, and the synthesized [Fe3O(A2)3][Ni2(B1)3X6] was repeatedly washed with DMF and dried at 55°C for 12 h.

[0063] Example 3

[0064] Synthesis of metal-organic framework materials [Fe3O(A)3][Ni2(B)3X6] modified with pore structure units containing different special functional groups

[0065] In a Teflon stainless steel reaction vessel, FeCl3·6H2O (251.5 mg, 0.9 mmol), Ni(NO3)2·6H2O (204.8 mg, 0.7 mmol), 0.9 mmol of an organic ligand (I) containing a functional group structure (terephthalic acid, 2-hydroxyterephthalic acid, 2-mercaptoterephthalic acid, 2-bromoterephthalic acid, 2-chloroterephthalic acid, 2-aminoterephthalic acid, 2-nitroterephthalic acid, 2,5-dibromoterephthalic acid, 2,5-dichloroterephthalic acid, 2,5-dihydroxyterephthalic acid, tetrafluoroterephthalic acid, 2-formylaminoterephthalic acid or 2,5-di The mixture was dissolved in 3.0 g of N,N-dimethylformamide (DMF) by ultrasonication, and then 300 mg of trifluoroacetic acid (TFA) was added. After magnetic stirring for 2 h, nickel foam (NF) was placed as a conductive substrate, and the Teflon stainless steel reaction container was sealed in a stainless steel autoclave and heated in an oven at 150 ° C for 24 h. After cooling to room temperature, the solid and liquid were separated, and the synthesized [Fe3O(A)3][Ni2(B)3X6] was repeatedly washed with DMF and dried at 55 ° C for 12 h.

[0066] As a variation of the above embodiment, the conductive substrate may not be added during the synthesis process, and the metal organic framework powder material is loaded onto the conductive substrate after the synthesis. The conductive substrate may be nickel foam, carbon fiber paper or copper sheet, preferably nickel foam.

[0067] Comparative Example 1

[0068] Synthesis of Metal-Organic Framework Material [Fe3O(A2)3]

[0069] In a Teflon stainless steel reaction vessel, FeCl3·6H2O (251.5 mg, ~0.9 mmol) and 2-hydroxyterephthalic acid (169.8 mg, ~0.9 mmol) were first ultrasonically dissolved in 3.0 g of N,N-dimethylformamide (DMF), followed by the addition of 320 mg of trifluoroacetic acid (TFA). After magnetic stirring for 2 h, nickel foam (NF) was placed as a conductive substrate, and the Teflon was sealed in a stainless steel autoclave and heated in an oven at 150°C for 24 h. After cooling to room temperature, the synthesized [Fe3O(A2)3] was repeatedly washed with DMF and dried at 55°C for 12 h.

[0070] Comparative Example 2

[0071] Synthesis of γ-NiFeOOH: 2 mmol of Ni(NO3)2·6H2O and 2 mmol of Fe(NO3)3·9H2O were dissolved in 45 mL of dimethylformamide (DMF). Then 6 mL of aqueous solution containing 0.9 mmol of NaOH was added dropwise. After stirring at room temperature for 30 minutes, it was immersed in a homogeneous solution and heated at 120 ° C for 6.5 hours in a 100 mL polytetrafluoroethylene-lined stainless steel autoclave. After cooling to room temperature, it was washed three times with deionized water and ethanol, and then dried at 80 ° C to obtain γ-NiFeOOH.

[0072] Comparative Example 3

[0073] Synthesis of γ-FeOOH: 4 mmol of Fe(NO3)3·9H2O was dissolved in 45 mL of dimethylformamide (DMF). Then 6 mL of aqueous solution containing 0.9 mmol of NaOH was added dropwise. After stirring at room temperature for 30 min, it was immersed in a homogeneous solution and heated at 120 °C for 6.5 h in a 100 mL polytetrafluoroethylene-lined stainless steel autoclave. After cooling to room temperature, it was washed three times with deionized water and ethanol, and then dried at 80 °C to obtain γ-FeOOH.

[0074] Comparative Example 4

[0075] Synthesis of β-FeOOH: 1.350 g of FeCl3·6H2O was dissolved in 10 mL of deionized water and stirred for 10 min, then the mixed solution was transferred to a 20 mL polytetrafluoroethylene-lined stainless steel autoclave and kept at 120 °C for 12 h. After the autoclave was cooled naturally, the product was collected by centrifugation, washed three times with deionized water and ethanol, and finally dried in a vacuum oven at room temperature for 6 h.

[0076] Comparative Example 5

[0077] Synthesis of β-FeOOH / Ni(OH)2: 1.275mmol of nickel nitrate hexahydrate and 3.75mmol of urea were dissolved in 15mL of deionized water, and 1g of β-FeOOH was added. The solution was then transferred to a 20mL polytetrafluoroethylene-lined autoclave. The autoclave was heated to 100°C and kept for 3 hours. The obtained β-FeOOH / α-Ni(OH)2 was washed several times with ethanol and deionized water, and then vacuum dried at 60°C overnight.

[0078] Structural characterization and performance testing of materials in embodiments and comparative examples

[0079] like Figure 1 As shown in a to 1c, the crystal phases of [Fe3O(A2)3], [Fe3O(A2)3] [Fe2(B1)3X6] and [Fe3O(A2)3] [Ni2(B1)3X6] were studied by powder X-ray diffraction (PXRD). The experimental PXRD patterns of these metal organic framework powders were consistent with the simulated diffraction patterns, indicating that the materials were successfully synthesized. Among them, [Fe3O(A2)3] powder showed strong diffraction peaks at 7.34°, 8.84°, 10.05°, 12.45°, 16.08°, 16.84° and 17.68°, which corresponded to the (100), (101), (002), (102), (112), (103) and (202) crystal planes of the MIL-88B(Fe) structure (CCDC: 2088535), respectively, indicating that its crystallinity is excellent. It is worth noting that due to the insertion of [Ni2(B1)3X6] and [Fe2(B1)3X6] fragments into the MIL-88B(Fe) structure, the XRD diffraction peaks of [Fe3O(A2)3][Fe2(B1)3X6] and [Fe3O(A2)3][Ni2(B1)3X6] show significant differences in position and intensity compared with [Fe3O(A2)3].

[0080] To further verify the insertion of [Ni2(B1)3X6] and [Fe2(B1)3X6] fragments (collectively referred to as [M22(B1)3X6] fragments) into the MIL-88B(Fe) structure and to evaluate the introduction degree and water stability of [M22(B1)3X6] fragments, the synthesized powder samples were immersed in water and stirred for 1 day. Figure 1 As shown in Figure d, the newly formed XRD peaks of the [Fe3O(A2)3] sample after immersion for 1 day are at 9.16°, 9.46°, 10.7°, 16.6° and 18.2°, which belong to the (002), (100), (101), (103) and (200) crystal planes of MIL-88B(Fe) in H2O (CCDC:1485530), further confirming the “breathing” effect of the lattice. It is worth noting that, as Figure 1As shown in Figures 1e and 1f, when the [M22(B1)3X6] fragment is inserted into the [Fe3O(A2)3] structure, the crystal no longer shows shrinkage, which indicates that the [M22(B1)3X6] fragment has been successfully inserted into the [Fe3O(A2)3] structure to form the [Fe3O(A2)3][M22(B1)3X6] structure.

[0081] In addition, if Figure 2 As shown, no significant changes were observed in the Fourier transform infrared spectra (FT-IR) of the [Fe3O(A2)3] framework and [M22(B1)3X6]-modified [Fe3O(A2)3][M22(B1)3X6] before and after the water stability test, indicating that although the [Fe3O(A2)3] framework shrank, it maintained the same spatial coordination.

[0082] Figure 3 The N2 adsorption-desorption isotherm revealed that the BET specific surface area of ​​[Fe3O(A2)3][Ni2(B1)3X6] is 34.9 m 2 / g, which is higher than the specific surface area of ​​[Fe3O(A2)3] (8.2m 2 / g). The two metal organic framework catalysts showed obvious adsorption hysteresis loops, which are typical features of type III isotherms and indicate that they have microporous properties. The measured pore sizes of [Fe3O(A2)3][Ni2(B1)3X6] and [Fe3O(A2)3] are mainly concentrated at 0.68nm and 1.59nm, respectively, which is highly consistent with their crystal structures.

[0083] Furthermore, if Figure 4 The morphology of [Fe3O(A2)3], [Fe3O(A2)3][Fe2(B1)3X6] and [Fe3O(A2)3][Ni2(B1)3X6] samples was studied using scanning electron microscopy (SEM) and transmission electron microscopy (TEM). [Fe3O(A2)3] exhibits a uniform hexagonal bipyramidal morphology ( Figure 4 a), with an average diameter of about 3.5 μm and an average length of about 9.5 μm. When the [Fe2(B2)3X6] fragment is inserted into the [Fe3O(A2)3] structure, the morphology is still a hexagonal bipyramid ( Figure 4 b), but the average size is significantly reduced (average diameter is about 1.6 μm and average length is about 5.5 μm). In contrast, when the [Ni2(B2)3X6] fragment is inserted into the [Fe3O(A2)3] structure, the [[Fe3O(A2)3][Ni2(B1)3X6] crystals self-assemble into hexagonal prisms ( Figure 4 c).

[0084] Figure 5TEM images of [Fe3O(A2)3][Ni2(B1)3X6] show that hexagonal prisms with an average length of about 2.1±0.5μm and a thickness of about 220nm can be clearly seen in TEM and high-resolution TEM (HRTEM) images. Elemental mapping by TEM and energy dispersive X-ray spectroscopy (EDS) showed that the elements Fe, Ni, Cl, C, N and O are uniformly distributed in the [Fe3O(A2)3][Ni2(B1)3X6] hexagonal prisms, and the Fe:Ni ratio is close to 1:1.

[0085] In addition, high-resolution Fe 2p X-ray photoelectron spectroscopy (XPS) analysis of the catalyst [Fe3O(A2)3][Ni2(B1)3X6] can be decomposed into Fe 3+ The characteristic peaks of (712.2 and 725.6 eV) and their corresponding vibration satellite peaks (717.5 and 729.7 eV) Figure 6 Compared with [Fe3O(A2)3], the Fe 2p of [Fe3O(A2)3][Ni2(B1)3X6] moves toward the direction of low binding energy (the Fe 2p in [Fe3O(A2)3] 1 / 2 712.26 eV in [Fe3O(A2)3][Ni2(B1)3X6], while 712.04 eV in [Fe3O(A2)3][Ni2(B1)3X6], indicating a decrease in valence state, which is consistent with the XAS results. Figure 7 As shown in Figure 2, the Ni 2pXPS spectrum of the [Fe3O(A2)3][Ni2(B1)3X6] catalyst shows double peaks at 712.1 and 724.1 eV, which are attributed to Ni 2+ Compared with [Fe3O(A2)3], XPS analysis showed the presence of N and Cl in the catalyst [Fe3O(A2)3][Ni2(B1)3X6], indicating that the pore modification unit has been successfully introduced. The high-resolution C1s XPS spectrum also confirmed the composition of [Fe3O(A2)3][Ni2(B1)3X6]: the aromatic rings C=C / CC (284.7 eV), CO / CN (286.4 eV) and carboxyl groups (C=O, 288.8 eV) in these MOFs Figure 8 ).

[0086] Comprehensive understanding of the Fermi level (E F ), including the hybridization of transition metal 3d and O2p, is crucial for elucidating the relationship between the electronic structure of the catalyst and its catalytic activity. To this end, valence band XPS (VB-XPS) studies were performed to explore the changes in the frontier orbitals and the occupied and unoccupied density of states (DOS) near the Fermi level before and after the introduction of [M22(B1)3X6] ( Fig. 9 ).from Fig. 9 It can be seen that the occupied states in the valence band move toward the Fermi level after the introduction of [M22(B1)3X6]. The valence band of [Fe3O(A2)3][Ni2(B1)3X6] (1.27 eV) moves toward the low binding energy direction compared with pure [Fe3O(A2)3] (2.26 eV), indicating that the introduction of [Ni2(B1)3X6] effectively changes the electronic structure and promotes the charge transfer process in OER.

[0087] Fig.10 Figure 2 shows the initial electrocatalytic oxygen evolution performance of [Fe3O(A2)3], [Fe3O(A2)3][Fe2(B1)3X6] and [Fe3O(A2)3][Ni2(B1)3X6]. In the initial cycle, the [Fe3O(A2)3][Ni2(B1)3X6] catalyst was at 10 mA / cm 2 At a current density of 2.5 Å, it exhibited an overpotential of 226.8 mV and a Tafel slope of 49.8 mV / dec, which were lower than those of [Fe3O(A2)3] (251.1 mV, 58.4 mV / dec), [Fe3O(A2)3][Fe2(B1)3X6] (234.7 mV, 53.2 mV / dec) and IrO2 (335.8 mV, 98.6 mV / dec) catalysts. Fig.10 (a and b in the middle). The double layer capacitance (C dl ) value is estimated to be 2.87mF / cm 2 , slightly higher than [[Fe3O(A2)3] catalyst (2.19mF / cm 2 )( Fig.10 In addition, at a constant overpotential of 300 mV, the turnover frequency (TOF) of the [Fe3O(A2)3][Ni2(B1)3X6] catalyst was as high as 0.633 s. -1 , higher than several other catalysts ( Fig.10 (middle d figure).

[0088] In addition, in situ electrochemical Raman spectroscopy studies were performed to explore the active mechanism of the metal-organic framework during the oxygen evolution reaction (OER). Before applying an oxidative potential, [Fe3O(A2)3] showed a Raman peak at 683.9 cm-1 in the electrolyte, which was attributed to the Fe-O vibration mode ( Fig.11 ).like Fig.12As shown in a, in the in situ Raman spectrum of [Fe3O(A2)3], when the voltage is initially applied, the characteristic peak of Fe-O disappears; when the voltage is further increased to 1.24 V vs. RHE, two characteristic peaks at 669.2 cm-1 and 493 cm-1 appear, which are related to FeOOH; when the voltage is further increased to 1.84 V vs. RHE, the characteristic peak at 669.2 cm-1 moves significantly to a higher wave number, which is attributed to the change in the Fe-O bond length.

[0089] like Fig.11 As shown in Figure b, in the in-situ Raman spectrum of [Fe3O(A2)3][Fe2(B1)3X6], after voltage was applied, the characteristic peak at 683cm-1 shifted slightly to a higher wave number (1.24V vs.RHE), while the characteristic peak at 723cm-1 gradually decreased. When the voltage was further increased to 1.44V vs.RHE, the characteristic peak at 723cm-1 shifted to a lower wave number, indicating that the [Fe2(B1)3X6] unit underwent a reconstruction process to form FeOOH.

[0090] [Fe3O(A2)3][Ni2(B1)3X6] in the electrolyte shows two distinct characteristic Raman peaks at 531 cm-1 and 683 cm-1, which are attributed to the vibration modes of Ni-O and Fe-O, respectively. Fig.12 As shown in Fig. 2a, when the voltage is increased to 1.04 V vs. RHE, the intensity of the characteristic Fe-O peak decreases and moves to a higher wave number (686 cm-1). When the voltage is further increased to 1.24 V vs. RHE, the characteristic Fe-O peak moves to a lower wave number (674 cm-1), indicating that the Fe center has transformed to form FeOOH. When the voltage is further increased to 1.74 V, the peak at 475 cm-1 (δ(Ni III-O )) and 551cm-1(ν(Ni III-O The growth of a pair of new peaks in the graphene and chromatin is attributed to the e of NiOOH and g Bonding vibration and A 1g Stretching vibration bonds, which indicates that the catalyst undergoes structural reconstruction during the OER process. All results show that the reconstruction rate of the [Fe3O(A2)3] (Fe-O: carboxylic acid oxygen coordination) structural unit is faster than that of the inserted [M22(B1)3X6] unit (triazole coordinated Fe / Ni-N), among which the reconstruction rate of the [Fe2(B1)3X6] unit is faster than that of the [Ni2(B1)3X6] unit, and finally FeOOH and NiOOH are formed, respectively.

[0091] Raman and X-ray photoelectron spectroscopy (XPS) analysis showed that under the influence of electrolyte and potential operation, the MOF structure will undergo reconstruction, and the reconstruction process involves phase change, valence state and valence band adjustment. In order to reveal the relationship between the structural changes, kinetic behavior and OER performance of MOF reconstruction in real time, the present invention carried out continuous cyclic voltammetry (CV) cycles in the range of 1.1-1.6Vvs.RHE. The electrochemically active surface area (ECSA) and OER activity of [Fe3O(A2)3] and [Fe3O(A2)3][Ni2(B1)3X6] electrodes changed with the increase of CV cycle number. It is worth noting that the overpotential of [Fe3O(A2)3][Ni2(B1)3X6] dropped to the minimum value at the 200th cycle, at 100mA / cm 2 It reaches 263.1mV, which is 16.8mV lower than that in the first cycle ( Fig.13 ).

[0092] Due to the structural reconstruction of MOFs, as well as oxygen vacancies, bond length extension, and activation of oxygen on active sites, the energy barriers and kinetics of MOF-catalyzed reactions change significantly during the oxygen evolution reaction (OER), triggering changes in the intrinsic OER activity. Compared with the synthesized FeOOH catalyst, the FeOOH species generated by MOF self-reconstruction exhibited superior OER catalytic activity and a lower time constant ( ) under the same conditions. Fig.14 ). In situ Raman analysis combined with X-ray absorption spectroscopy, electron paramagnetic resonance (EPR) and Raman data in different cycles showed that the [Fe3O(A2)3] coordination structure was rapidly reconstructed into FeOOH during the OER process due to the presence of OH- and applied voltage. Compared with the MN structure coordinated by the azole, the reconstruction rate of the Fe-O bond coordinated by the carboxylic acid structure was faster. In addition, the reconstruction process of [M22(B1)3X6] was relatively slow. Initially, the water molecules and Cl- coordination in these two complexes were affected by OH-, resulting in partial coordination changes. In the [M22(B1)3X6] series, the reconstruction of the Fe-N bond coordination of [Fe2(B1)3X6] was ultimately faster than the reconstruction of the Ni-N bond coordination of [Ni2(B1)3X6].

[0093] Dynamic behavior is one of the key factors affecting the stability of electrocatalysis. Fig.15 As can be seen, at 500mA / cm 2 At a current density of 500 mA / cm, the potential remained stable within 120 h, and [Fe3O(A2)3][Ni2(B1)3X6] showed significantly better catalytic stability than the original [Fe3O(A2)3]. For [Fe3O(A2)3][Ni2(B1)3X6], when the current density was 500 mA / cm 2When the overpotential increased by only 9 mV, the overpotential of [Fe3O(A2)3] increased significantly by 33 mV. In addition, further X-ray diffraction (XRD) analysis showed that the material structure changed after the OER stability test. Scanning electron microscopy (SEM) images showed that the [Fe3O(A2)3][Ni2(B1)3X6] catalyst maintained its hexagonal structure after the OER stability test, but the catalyst surface became rougher ( Fig.16 Although [Fe3O(A2)3] remained stable for 120 h, its original morphology completely collapsed ( Fig.17 This is because [Fe3O(A2)3][Ni2(B1)3X6] contains non-planar binuclear triazole clusters with two metal ions arranged along the channel direction, making its size quite compact and ensuring that it will not collapse during the reconstruction process.

[0094] To investigate the application prospects of [Fe3O(A2)3][Ni2(B1)3X6] as a cathode material under actual industrial conditions, an electrolytic cell was constructed based on an anion exchange membrane electrolyzer (AEMWE). Surprisingly, the [Fe3O(A2)3][Ni2(B1)3X6] catalyst showed good conductivity at 1,000 and 2,000 mA / cm 2 The battery voltages of the IrO2-based battery are 1.9V and 2.3V, respectively, while the battery voltages of the IrO2-based battery are 2.5V and 3.0V, respectively. Fig.18 In order to further verify its practical application potential on an industrial scale, the present invention is carried out at 1,000 mA / cm 2 The electrolytic cell was tested for long-term stability for nearly 200 hours. Fig.19 ). Therefore, the synthesized [Fe3O(A2)3][Ni2(B1)3X6] catalyst undergoes a reasonable dynamic reconstruction due to structural factors, which affects its kinetic behavior and ensures long-term high-activity industrial stability, exceeding the catalytic activity and industrial stability of most reported anode catalysts.

[0095] The above-described embodiments only express the preferred implementation modes of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. The technical features of the embodiments can be arbitrarily combined. For the sake of brevity, all possible combinations of the technical features in the above-described embodiments are not described, but as long as there are no contradictions in the combinations involved, they should be considered to be within the scope of this specification. For those of ordinary skill in the art, several modifications and changes can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the claims.

Claims

1. An oxygen evolution catalyst based on a metal organic framework, characterized in that: The oxygen evolution catalyst comprises a metal organic framework and a pore structure modification unit inserted into the metal organic framework, wherein the metal organic framework is formed by a combination of an organic ligand A containing a dicarboxylic acid and a metal source reagent M1, and the pore structure modification unit is formed by a combination of a triazole organic ligand B and a metal source reagent M2, wherein the organic ligand A containing a dicarboxylic acid is one or more of the compounds represented by formula (I), and the triazole organic ligand B is one or more of the compounds represented by formula (II): in: In formula (I), the combination of R1 / R2 / R3 / R4 is A1: H / H / H / H; A2: OH / H / H / H, A3: SH / H / H / H, A4: NH2 / H / H / H, A5: NO2 / H / H / H, A6: Br / H / Br / H, A7: OH / H / OH / H, A8: Cl / H / Cl / H, A9: F / F / F / F, A10: NHCHO / H / H / H, A11: Cl / H / H / H, A12: Br / H / H / H, A13: NH2 / H / NH2 / H, A14: Br / H / H / H or A15: Cl / H / H / H; The combination of R5 / R6 in formula (II) is B1: H / H, B2: H / NH2, B3: H / NO2, B4: H / SH, B5: SH / CH3, B6: SH / NH2, B7: H / CH3, B8: H / CF3, B9: H / Br, B10: H / CN, B11: CH3 / CH3 or B12: NH2 / NH2.

2. The oxygen evolution catalyst according to claim 1, characterized in that: The metal source reagent M1 is an Fe salt, and the metal source reagent M2 is one or more of a Fe salt, a Fe salt, a Ni salt, a Co salt and a Mn salt.

3. The oxygen evolution catalyst according to claim 2, characterized in that: The metal source reagent M1 is FeCl3, and the metal source reagent M2 is one or more of FeCl2, FeCl3, Fe(NO3)2, Ni(NO3)2, Mn(OAc)2 and Co(OAc)2.

4. The oxygen evolution catalyst according to claim 1, characterized in that: The dicarboxylic acid-containing organic ligand A is 2-hydroxyterephthalic acid, and the triazole organic ligand B is 1,2,4-triazole or 3-amino-5-mercapto-1,2,4-triazole.

5. The method for synthesizing the oxygen evolution catalyst according to any one of claims 1 to 4, characterized in that The following steps are involved: Step (1): adding an organic ligand A containing a dicarboxylic acid, a triazole organic ligand B, a metal source reagent M1 and a metal source reagent M2 into an organic solvent S, and dissolving them to obtain a mixed solution a; Step (2): adding a synthesis reagent Q to the mixed solution a to obtain a mixed solution b; Step (3): subjecting the mixed solution b to a hydrothermal reaction at a temperature of 140 to 160° C. for 24 to 72 hours, and subjecting the product to solid-liquid separation, washing and drying.

6. The synthesis method according to claim 5, characterized in that: In step (1), the molar ratio of the dicarboxylic acid-containing organic ligand A to the triazole organic ligand B is 1:1 to 1.

2.

7. The synthesis method according to claim 5, characterized in that: In step (3), a conductive substrate is added into the hydrothermal reaction vessel.

8. The synthesis method according to claim 5, characterized in that: The organic solvent S is N,N-dimethylformamide.

9. The synthesis method according to claim 5, characterized in that: In step (2), the synthesis reagent Q is trifluoroacetic acid, and the mass ratio of the synthesis reagent Q to the organic ligand A of the dicarboxylic acid and the triazole organic ligand B is A+B:Q=1:1.2-1.

9.

10. Use of the oxygen evolution catalyst according to any one of claims 1 to 4 in oxygen evolution reaction by water electrolysis.

Citation Information

Patent Citations

  • Electrochemical catalyst as well as preparation method and application thereof

    CN111939984A

  • Method for preparing foamy carbon supported FeNi alloy catalyst from nitro-modified metal organic framework and application of foamy carbon supported FeNi alloy catalyst

    CN114293221A

  • Water electrolysis catalyst and preparation method therefor

    WO2024085318A1